2018
DOI: 10.3390/nu10111749
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Flavonoid Intakes Are Associated with Race but Not Income in an Urban Population

Abstract: Flavonoids are polyphenolic phytochemicals with health-promoting properties, yet knowledge about their intake in at-risk populations is limited. This study sought to estimate intakes of total flavonoids and six flavonoid classes in the Healthy Aging in Neighborhoods of Diversity across the Life Span (HANDLS) study; determine if differences in intakes exist by race (African American (AA) and White (W)) and income (< or >125% Federal poverty guidelines); and compare intakes to those of a nationally representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
1
5
1
Order By: Relevance
“…This finding is consistent with other studies (24,30,31) , being associated with higher intake of polyphenol-rich foods by females. We found that there was an increase in polyphenol classes intake with substantial differences according to ethnic groups, with medians significantly higher among White compared with other groups, which corroborate results from other studies (32,33) . Phenolic acids intake increased with age in the two NDS editions, and the flavonoid intake reduced across adolescents in 2017–2018 compared with 2008–2009.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with other studies (24,30,31) , being associated with higher intake of polyphenol-rich foods by females. We found that there was an increase in polyphenol classes intake with substantial differences according to ethnic groups, with medians significantly higher among White compared with other groups, which corroborate results from other studies (32,33) . Phenolic acids intake increased with age in the two NDS editions, and the flavonoid intake reduced across adolescents in 2017–2018 compared with 2008–2009.…”
Section: Discussionsupporting
confidence: 91%
“…There was a socioeconomic gradient in flavonoid intake both in France and in the US [ 23 , 24 , 27 ], though income effects in the US were not always consistent [ 27 ]. Consistent with the present results, the highest total flavonoid intake in the US was found in adults aged 51–70 y (293 mg/d), and in groups with college education (251 mg/d) and with higher incomes (IPR > 3.5:249 mg/d) ( p < 0.001 for all).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a stronger correlation between total flavonoids intake and the WWI had been noted in individuals with PIR below 1.3. This could be attributed to disparities in the primary sources of flavonoids between lower and higher socioeconomic groups, with lower-income families potentially engaging more frequently in home-cooked meals, which may influence their dietary flavonoid intake ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%